SISTEM KOORDINAT ROBOT INDUSTRI - Purwanto, Adi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2006)
Manipulator or Industrial Robo is an equipment wich designed to manipulate human hand motion. Robot is belonging to industrial automation technology there are rapid development progress according to computer technology progress that able to make programmable automations. Robot is one of implementation programmable automation. In order to subtitute human labour by robot, there are many aspect must be considered, susch as: technical aspect, economical aspect, social and environment work conditions. Select and design of robot type, needed knowledge about joint, coordinate system or robot configuration, and work envelope. So, selecting robot type can work optimally.